Effect of Different Floor Space Allowances on Body Weight Changes, Voluntary Feed, Nutrients, and Water Intake in Indigenous Sheep - Khimani, Sagar S; Patel, Yogesh G; Modi, Rakesh J; Trivedi, Manoj M (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
Present study was conducted on 45 adult dry non-pregnant (25-30 kg) farm born indigenous ewes. The animals were divided into three  treatment groups, i.e., T1: 1.5 m2 (4 animals in each pen), T2: 1.25 m2 (5 animals in each pen) and T3: 1.0 m2 (6 animals in each pen) floor  space allowances with three replications in each treatment. The animals were maintained on farm feeding for 42 days of experiment  with 15 days of adaptation period. The body weight of experimental animals was not influenced significantly (p
Keywords: Dry matter intake; Floor space; Indigenous ewes; Nutrient intake; Water intake